Seasonality of halogen deposition in polar snow and ice - Spolaor, Andrea; VALLELONGA, PAUL TRAVIS; GABRIELI, Jacopo; COZZI, Giulio; TURETTA, Clara; BARBANTE, Carlo; Martma, T.; Björkman, M. P.; Isaksson, E.; Kjær, H. A.; Curran, M. A. J.; Moy, A. D.; et al. (Atmospheric Chemistry and Physics, 2014)
The atmospheric chemistry of iodine and bromine in Polar regions is of interest due to the key role of halogens in many atmospheric processes, particularly tropospheric ozone destruction. Bromine is emitted from the open ocean but is enriched above first-year sea ice during springtime bromine explosion events, whereas iodine emission is attributed to biological communities in the open ocean and hosted by sea ice. It has been previously demonstrated that bromine and iodine are present in Antarctic ice over glacial-interglacial cycles. Here we investigate seasonal variability of bromine and iodine in polar snow and ice, to evaluate their emission, transport and deposition in Antarctica and the Arctic and better understand potential links to sea ice. We find that bromine and iodine concentrations and Br enrichment (relative to sea salt content) in polar ice do vary seasonally in Arctic snow and Antarctic ice. Although seasonal variability in halogen emission sources is recorded by satellite-based observations of tropospheric halogen concentrations, seasonal patterns observed in snowpack are likely also influenced by photolysis-driven processes. Peaks of bromine concentration and Br enrichment in Arctic snow and Antarctic ice occur in spring and summer, when sunlight is present. A secondary bromine peak, observed at the end of summer, is attributed to bromine deposition at the end of the polar day. Iodine concentrations are largest in winter Antarctic ice strata, contrary to contemporary observations of summer maxima in iodine emissions. These findings support previous observations of iodine peaks in winter snow strata attributed to the absence of sunlight-driven photolytic re-mobilisation of iodine from surface snow. Further investigation is required to confirm these proposed mechanisms explaining observations of halogens in polar snow and ice, and to evaluate the extent to which halogens may be applied as sea ice proxies. The atmospheric chemistry of iodine and bromine in Polar regions is of interest due to the ...